Comparison of the Efficacy of Duloxetine and Pregabalin in Pain Relief Associated with Diabetic Neuropathy - Shahid, Wajeeha (Cureus, 2019)
Introduction Painful diabetic peripheral neuropathy (PDPN) complicates 25% of type II diabetes mellitus. It has a profound impact on diabetes-related morbidity and worsens the quality of life. Both pregabalin and duloxetine may be indicated for PDPN. In this study, the efficacy of duloxetine and pregabalin was compared in patients with PDPN. Methods It was a single-centre open-label study conducted with patients of diabetes mellitus type II diagnosed with PDPN. Patients were randomized to receive 60 mg/daily duloxetine or 300 mg/daily pregabalin. Pain scores were recorded using visual analogue scale (VAS) on day 0, week 4, and week 12. Data was entered and analysed using SPSS version 22.0 (IBM Corp., Armonk, NY). Results In the duloxetine group, the mean VAS score decreased from 6.81 ± 0.91 to 4.01 ± 1.12 with 12 weeks of therapy (p <0.0001). In the pregabalin group, the mean VAS score decreased from 6.99 ± 1.12 to 4.91 ± 0.82 with 12 weeks of therapy (p <0.0001). At 12 weeks, duloxetine showed lower VAS scores than pregabalin (p <0.0001). In the duloxetine group, the mean change in VAS score over time was - 2.80 and in the pregabalin group, the mean change was - 2.80. Adverse events were reported in 17.9% of the participants. Lethargy/somnolence (8.1%) and peripheral edema (3.4%) were commonly reported in the pregabalin group and constipation (6.9%) and orthostatic hypotension (4.6%) were commonly reported in the duloxetine group. Conclusions Duloxetine at a daily fixed dose of 60 mg is efficacious in the relief of neuropathic pain. Pregabalin also showed a comparable outcome. Both duloxetine and pregabalin have a promising safety profile and are well-tolerated.